“Estudio de la presencia de hongos trichoderma, beauveria y aspergillus en suelos agrícolas de la asociación de productores agroecológicos de Tungurahua en el año 2023”. - Gualavisí Gómez, Amanda Verónica (2023)
The purpose of this research is to analyze the presence of existing fungi in the agricultural soils of the association of agroecological producers of Tungurahua (PACAT). The methodology used had an investigative and field emphasis, in the field phase, samples were collected in 4 cantons, 9 associations, 42 producers, in the laboratory phase 10 g of each sample was taken, which were diluted to -1, placing 0.5 ml of mother solution in petri dishes with PDA, sealed with coding and placed in an incubator at an average temperature of 27ºC, for 8 days a daily observation was made to see if the presence of fungi, obtaining as a result that of the 425 samples, 5% could not observe the presence of fungi. For its microscopic identification, a bit of the fungus was taken and according to its color and microscopic characteristics, the species found were: Trichoderma, Beauveria and Aspergillus.